ПЛАСИРАЊЕ ИДЕОЛОГИЈЕ У КОНТЕКСТУ ЕМАНЦИПАЦИЈЕ ФИЛМА ОД НАРАТИВА ПУТЕМ АТМОСФЕРЕ - Krašovec, Primož (Srpska politička misao, 2025)
As advertising transitioned from intrusive propaganda to seductive experience it freed its visual dimension from the constraints of representation and allowed it to develop in a process of free experimentation, much like the avant-garde tendencies in contemporary art. When this new aesthetic, first developed in culturally marginal genres such as advertising and music videos, found its way into cinema, it also began to transform TV series and later films, allowing them to break free from narrative and exploit the full potential of film as technology.With its emancipation from narrative tied to literature and theatre, cinema became less representational and oriented towards human stories and increasingly science-fictional at the level of (visual) form. This process thus opens up new aesthetic and technological perspectives that appear alien in their distinction from the narratives we were used to in classic cinema. At the same time, this new, technologically mutated cinema also tends towards horror at the level of content—horror in the sense of alien atmospheres that disrupt and undermine narrative.In this paper we will illustrate this transition from cinema, based on narrative, to cinema, based of atmosphere, through an analysis of several cases: TV series Euphoria and Too Old to Die Young as examples of “atmosphere placement” replacing “ideology placement” as well as several examples from recent science fiction and horror cinema as new, atmospheric cinema and—as such—contemporary avant-garde.
Keywords: пласирање идеологије; атмосфера; научна фантастика; хорор; кинематографија; технологија; страност